Edukasi Gizi Seimbang dan Makanan Sehat untuk Imunitas Tubuh dalam Kondisi Pandemi Covid-19 di SMPN 2 Bayang, Kabupaten Pesisir Selatan - Putri Aulia Arza; Yeffi Masnarivan; Dhiya Fahdila Rahmah; Afifah Khairani Ananda (Warta Pengabdian Andalas, 2020)
Consumption of foods that can increase body immunity and are nutritionally balanced for school children especially in the current conditions amid the Covid-19 pandemic. SMPN 2 Bayang is one of the junior secondary schools located in Bayang District, Pesisir Selatan Regency. Healthy eating habits are the most important behaviors that can affect the state of nutrition and health of a person so that it is hoped that through education on balanced nutrition and healthy food for body immunity. The purpose of this community service is to increase junior high school students' knowledge about nutritionally balanced food and increase body immunity. The service began with an introduction to the approach to students and was continued with a pre-test. The next activity is nutrition education in the form of providing materials and simulations in preparing a balanced nutrition menu using video media, post-tests, and question and answer with prizes with community service participants. Participants and school principals were very enthusiastic in participating in the activity, because it was considered very important in the Covid-19 pandemic. From the pre-test and post-test results, it was concluded that there was a significant difference between the level of knowledge before and after nutrition education.